Implementation of E-Learning and Organizational Commitment Towards the Performance of KPPS Members (Voting Organizing Group) in the 2024 Election in Cirebon Regency - Rizki Pidia Pratiwi; Dimas Haris Amarudin; Noveria Susijawati (Indonesian Interdisciplinary Journal of Sharia Economics)
This study aims to analyze the effect of E-Learning and Organizational Commitment on the Performance of KPPS (Polling Organizing Group) members in the implementation of the 2024 Election in Cirebon Regency. In the context of increasing challenges and complexities in the implementation of elections, strengthening human resource capacity through digital training and strengthening commitment to the organization is crucial. The research method used is quantitative with data collection techniques through questionnaires to 150 KPPS member respondents. The results of the analysis show that both E-Learning and Organizational Commitment partially and simultaneously have a significant effect on the performance of KPPS members. E-Learning has been shown to improve understanding of material and work efficiency, while Organizational Commitment encourages emotional involvement and moral responsibility for tasks. These findings indicate that the combination of technology-based training and internalization of organizational values can increase the effectiveness and professionalism of election organizers. This study suggests the importance of optimizing e-learning platforms and strengthening commitment strategies to support the success of future elections.